Extending development of web application system with location data - Mohamad Aqib Haqmi, Abas; Ihsan, Mohd Yassin; Megat Syahirul Amin, Ali; Nooritawati, Md Tahir; Azlee, Zabidi (Institute of Electrical and Electronics Engineers Inc., 2021)
Web applications systems or known as 'web apps' are useful tools to allow information to reach to end users as efficiently as possible. End users of the applications only require a web browser and internet to consume information no matter where or when. Location is an important data that gives valuable information and insights for the decision making process. Integrating the location data of users in web application systems through location based service brings a lot of benefits for future application of predictive analysis and recommender systems. This paper objective is to extend the development of the current web application system with a location based service. The result shows the extension on adding location based data with gps coordinate latitude and longitude in the system.